The Impact of Autistic Traits on Self-Recognition of Body Movements - Burling, Joseph M.; Kadambi, Akila; Safari, Tabitha; Lu, Hongjing (Frontiers in Psychology, 2019)
Despite the sparse visual information and paucity of self-identifying cues provided by point-light stimuli, as well as a dearth of experience in seeing our own-body movements, people can identify themselves solely based on the kinematics of body movements. The present study found converging evidence of this remarkable ability using a broad range of actions with whole-body movements. In addition, we found that individuals with a high degree of autistic traits showed worse performance in identifying own-body movements, particularly for simple actions. A Bayesian analysis showed that action complexity modulates the relationship between autistic traits and self-recognition performance. These findings reveal the impact of autistic traits on the ability to represent and recognize own-body movements.